An evaluation of appreciative inquiry as an alternative organisation development approach - Van der Merwe, Schalk Willem (Rhodes University, Faculty of Commerce, Department of Management, 2017)
The research provides an insight into the main challenges of previous Organisation Development processes, and Appreciative Inquiry is explored to establish the value it can offer as an alternative which minimises these challenges in today's organisations. Organisation Development originated during the early 1950s and has evolved, adapted and changed dramatically since then. Two classical Organisation Development processes, Lewin's 3-Step model and the Action Research spiral, are described, and typical challenges of applying them in today's organisations are outlined. To remain competitive, organisations need to identify, adjust, and adapt to changing circumstances. These changing circumstances are constant and are due to increasingly complex demands from technological, economic, managerial, and cultural needs. Appreciative Inquiry as an approach is explored as an alternative Organisation Development process: it shifts the question from 'what is going wrong' to 'what is going right in the organisation'. Appreciative Inquiry consists of the Discovery, Dream, Design and Destiny stages, and searches for the best in people and their organisations. In accordance with the constructionist paradigm, the research offers conclusions through the confirmation of past practices, conversations and relationships combined with creative new methods or experimentation of a positive intended future. The One- Group Pretest-Posttest, as a design, was selected to explore the effect of the variable (the Appreciative Inquiry intervention) in relation to the pre- and post-experimental evaluation. The design consists of an initial engagement (Pretest), the influencing variable (an Appreciative Inquiry intervention) and final engagement (Posttest) with the same group. The research was supported by a mixed method approach, with qualitative data supported by quantitative data. The quantitative data provided a general understanding of how participants experienced the change interventions. The qualitative data provided the information on how respondents experienced Organisation Development before an Appreciative Inquiry intervention and their views after an Appreciative Inquiry intervention. A South African secondary school was selected as a research site. Limited research is available regarding the application of Organisation Development and especially Appreciative Inquiry as a process in schools in general, and in South African schools in particular. A survey questionnaire was the instrument for collecting the quantitative data regarding the participants' biographical information and change process perceptions. For the collection of qualitative data, interview questionnaires were used. The findings indicate that whereas previous change processes appear to have regarded the various staff levels of the school as separate entities, during the Appreciative Inquiry approach all staff were included as being an integral part of the organisation. The main finding after completion of the Appreciative Inquiry intervention was that collectively discussing and defining issues in a positive light instead of a problem to be solved changes the perspective of participants. Through the application of the Appreciative Inquiry's four stages, participants were invited to think in a new way by applying innovation, enhancing participation, maintaining a positive core, and providing practical solutions through provocative statements. Conclusions reached from the research are that Appreciative Inquiry is a viable alternative for minimising Organisation Development challenges in contemporary organisations. The conclusions are based on factors such as understanding the reason for change; strong leadership; defining what is a successful intervention; understanding the Appreciative Inquiry process, the value of provocative statements; and the sustainability of change.
Keywords: Uncatalogued